Identity Around Multilingualism: - Radia Al Rashid Radia Al Rashid (Crossings, 2023)
As no country houses people speaking solely one language in the present world, various studies regarding the use of multilingualism were done over the years not only in the field of empirical research but also in literary contexts. Code-switching has been the most researched phenomenon in literary language from a multilingual perspective. The debate between considering literary characters as real-life human beings or merely textual constructs has intensified over the years. Subsequently, a middle ground combining both humanizing and non-humanizing aspects of literary characters emerged. In this study, I analyze the use of multilingualism in a literary character’s portrayal by examining her linguistic identity through her behaviors involving language use and comprehension. Yolanda, the second daughter of the De La Torre family depicted in the novel, How the Garcia Girls Lost Their Accents, written by Julia Alvarez in 1991, is the target character for this study. Using a qualitative research approach, Yolanda’s character is analyzed by using the characterization model developed by Culpeper in 2001. Three textual cues, namely explicit, implicit, and authorial, are examined in the descriptions and language uses of Yolanda’s character. The outcomes of the study not only portray Julia Alvarez’s philosophy and attitude regarding multilingualism, but also show Yolanda’s unique traits, struggles, confusion, liminality, and linguistic position in the world of the novel.